2014
DOI: 10.1108/ijmpb-09-2013-0043
|View full text |Cite
|
Sign up to set email alerts
|

The role of agency in project initiation decisions

Abstract: Purpose – The purpose of this paper is to explore the role of decision rules and agency in supporting project initiation decisions, and the influences of agency on decision-making effectiveness. Design/methodology/approach – The study this paper is based upon used grounded theory methodology, and sought to understand the influences of individual decision makers on project initiation decisions within organizations. Data collection involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…• negotiations Conceptual article, development of a negotiation framework (Mullaly, 2014) Process and political constraints in project initiation decisions…”
mentioning
confidence: 99%
“…• negotiations Conceptual article, development of a negotiation framework (Mullaly, 2014) Process and political constraints in project initiation decisions…”
mentioning
confidence: 99%
“…The pluralist school focuses on opportunistic behaviour based on self-interest and environmental factors such as contractual relationships and organisational politics (e.g. Flyvbjerg, 2007;Mullaly, 2014;Pinto, 2014). The potential to quantify perceptions of environments at the individual level with the individual level BWS object case enables a Heterogeneous individual perceptions range of large-scale research in this school.…”
Section: Large-scale Pluralist School Example Applicationmentioning
confidence: 99%
“…191-194) identify four criteria that indicate an actor's agency: the actor must be able to make a difference; the actions must be intentional; there must be room for free play on the part of the actor; and the actor must be reflexive, in that they must be aware that they are exercising agency. Mullaly (2014) found that effective decision makers considered themselves as flexible, resilient or exercising initiative and followed rules and processes pragmatically with a focus on the fit and relevance of the rules and regulations to the perceived context. This suggests that multiple actors, each with their own sense of agency and what their cultural norms lead or guide them to do, may influence each other.…”
Section: Sensemaking Practice Through Use Of the Cultural-cognitive Pmentioning
confidence: 99%